ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS KOTA MADIUN : ANALYSIS OF THE COMMUNITY SATISFACTION INDEX FOR HEALTH SERVICES AT THE MADIUN CITY HEALTH CENTER - Alfiyani, Lina; Karlinda; Nikmah Ayu Ramadhani Amir; Eny Pemilu Kusparlina; Nurul Fatimah; Widya Kaharani Putri; Anindita Hasniati Rahmah; Asmirati Yakob; Danar Rista Saputra; Arif Setiawan; Ivando Zeldha Damara; Herdiyanto; Suharyo (Intan Husada : Jurnal Ilmiah Keperawatan, 2024)
Background. Public satisfaction with public services plays an important role in the stability of a country's health services. Measurement of the Public Satisfaction Index is a reference in evaluating the quality of service between patient expectations and health service performance.Purpose. This study aims to analyze the Community Satisfaction Index for Health services at the Madiun City Health Center.Methods. This study used a crosectional design with quantitative methods, conducted in October 2023 at the Madiun City Health Center with a sample of 64 research subjects using a simple random sampling technique. The research variables were 9 elements of the Community Satisfaction Index, namely the elements of requirements, procedures, time, rates, service products, competence, behavior, handling complaints, and facilities and infrastructure.Result. The results showed that the Community Satisfaction Index was 81.99, with details of the Community Satisfaction Index being good, namely in the elements of requirements (81.3%), procedures (71.9%), time (84.4%), service products (87.5%), competence (81.3%), behavior (71.9%), handling complaints (70.3%), with a very good Community Satisfaction Index in the elements of tariffs (62.5%) and facilities and infrastructure (79.7%).Conclusion. The Public Satisfaction Index is 81.99, with a very good Public Satisfaction Index on the elements of tariffs and facilities and infrastructure.